A tuneable method for N-debenzylation of benzylamino alcohols. - Grayson, E; Davis, B (2005)
[reactions: see text] N-Iodosuccinimide provides a mild, convenient, and tuneable reagent for the selective mono- or didebenzylation in representative, multifunctionalized carbohydrate and amino acid derived N-dibenzylamines with neighboring O-functionality.